An adaptive sliding mode fault-tolerant control of variable speed reaching law for steer-by-wire systems - Jinwen Yang; Yinquan Yu; Dequan Zeng; Yiming Hu; Junhui Liu; Kai Liu; Giuseppe Carbone; Shaohua Luo; Xiaofeng Zhu (Scientific Reports)
Abstract Fault-tolerant control (FTC) is crucial for enhancing the safety, reliability, and tracking performance of steer-by-wire (SBW) systems. This paper focuses on actuator effectiveness reduction faults and establishes an analytical model of the SBW system that incorporates motor disturbances, steering feedback, and self-aligning torque characteristics. To solve the inadequate tracking accuracy resulting from actuator fault and system disturbances, an adaptive sliding mode fault-tolerant control strategy based on a variable-speed reaching law (VSRL-ASMFTC) is proposed. By integrating an adjustment function into the constant-velocity reaching polynomial and designing an adaptive law, dynamic updating of the control law is achieved. Furthermore, the closed-loop stability of the system is proven based on Lyapunov’s stability criterion. The example information demonstrates that the proposed method reduces the root mean square (RMS) of tracking error by nearly 40% in three typical conditions compared to adaptive fault-tolerant control methods (ASMFTC), and the disturbances of the controller are relatively slighter. This indicates that the VSRL-ASMFTC mitigates system chattering, optimizes the system’s anti-disturbance capability and robust stability, and improves fault tolerance efficiency in the presence of actuator failures. It maintains good tracking performance of the system, which provides a basis for the design of high-performance fault-tolerant control strategies.